2018
DOI: 10.1105/tpc.18.00111
|View full text |Cite
|
Sign up to set email alerts
|

A Suppressor Screen for AGO1 Degradation by the Viral F-Box P0 Protein Uncovers a Role for AGO DUF1785 in sRNA Duplex Unwinding

Abstract: In , ARGONAUTE1 (AGO1) plays a central role in microRNA (miRNA) and small interfering RNA (siRNA)-mediated silencing and is a key component in antiviral responses. The polerovirus F-box P0 protein triggers AGO1 degradation as a viral counterdefense. Here, we identified a motif in AGO1 that is required for its interaction with the S phase kinase-associated protein1-cullin 1-F-box protein (SCF) P0 (SCF) complex and subsequent degradation. The AGO1 P0 degron is conserved and confers P0-mediated degradation to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 92 publications
(136 reference statements)
6
75
0
1
Order By: Relevance
“…Because these defects in root meristem activity might originate during embryogenesis, we aimed to deplete AGO1 postembryonically. For this, we used the b-estradiol-inducible (XVE:P0) line to express the F-box protein P0 from Turnip yellows virus, which induces the degradation of plant AGO proteins (Derrien et al, 2018). Upon P0 induction, both the root length and the root apical meristem size were significantly reduced ( Figures 1A and 1B) and thus recapitulated the phenotype observed in strong ago1 mutant alleles.…”
Section: Ago1 Depletion Affects Arabidopsis Cell Division and Root Mementioning
confidence: 72%
See 2 more Smart Citations
“…Because these defects in root meristem activity might originate during embryogenesis, we aimed to deplete AGO1 postembryonically. For this, we used the b-estradiol-inducible (XVE:P0) line to express the F-box protein P0 from Turnip yellows virus, which induces the degradation of plant AGO proteins (Derrien et al, 2018). Upon P0 induction, both the root length and the root apical meristem size were significantly reduced ( Figures 1A and 1B) and thus recapitulated the phenotype observed in strong ago1 mutant alleles.…”
Section: Ago1 Depletion Affects Arabidopsis Cell Division and Root Mementioning
confidence: 72%
“…Upon P0 induction, both the root length and the root apical meristem size were significantly reduced ( Figures 1A and 1B) and thus recapitulated the phenotype observed in strong ago1 mutant alleles. Because P0 triggers the degradation of several, if not all, plant AGOs (Baumberger et al, 2007;Derrien et al, 2018), we also induced P0 expression in the ago1-57 genetic background, expressing a mutated form of AGO1 resistant to P0mediated degradation (Derrien et al, 2018). The strong effect of P0 on meristem size and cell division activity was significantly suppressed in ago1-57 ( Figures 1A and 1B), indicating that this phenotype is mainly dependent on AGO1.…”
Section: Ago1 Depletion Affects Arabidopsis Cell Division and Root Mementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, investigations have shown that certain VSRs could mediate the degradation of various factors within the RNA silencing pathway. The polerovirus P0 protein has been shown to identify the degron in the DUF1785 domain of AGO1 and trigger degradation of AGO1 through the autophagy pathway (Baumberger et al, 2007;Bortolamiol et al, 2007;Csorba et al, 2010;Derrien et al, 2012Derrien et al, , 2018 and the P25 of Potato virus X interacts with and mediates degradation of AGO1 through the proteasome pathway (Chiu et al, 2010). The VPg encoded by Turnip mosaic virus (TuMV) potyvirus mediates degradation of SGS3 via ubiquitination and autophagy pathways (Cheng & Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the PIWI domain shows similarity to RNase H and is essential for target cleavage (Song et al, 2004;Parker et al, 2005). Finally, the N-terminal domain fragment (DUF1785) was recently described as being important for RNA duplex unwinding (Derrien et al, 2018).…”
mentioning
confidence: 99%